Density and characteristics of Green mussels (Perna viridis) in Percut Sei Tuan coastal, North Sumatra, Indonesia - IPANNA ENGGAR SUSETYA; Mohammad Basyuni; DESRITA DESRITA; ARIDA SUSILOWATI; TADASHI KAJITA (Society for Indonesian Biodiversity, 2021)
Percut Sei Tuan is a coastal area on the east coast of North Sumatra which has a lot of natural resource potential, one of them which is green mussels (Perna viridis). Green mussels have many benefits, namely for consumption, cultivation and bioindicator. This study aimed to determine the density, habitat location, growth pattern, frequency distribution of green mussels, physical-chemical parameters of water, a substrate of the bottom waters, and the relationship of green clams density to water and substrate parameters. The study was conducted in July-September 2020. Data analysis included density, the relationship of total length and weight of green mussels, the frequency distribution of shell lengths, and Principal Component Analysis (PCA). The results showed that the density of green mussels at stations I, II, and III were 352 ind/m2, 3 ind/m2, and 1 ind/m2, respectively. The relationship between the length and weight of green shells shows that the growth was negative allometric. The water condition, seen from the physical, chemical, and substrate parameters, was still suitable for P. viridis. Water and substrate parameters that were positively related to the density of green mussels were water temperature, nitrate, phosphate, C-organic, percentage of silt and clay. Parameters that were negatively related were salinity, pH, and percentage of sand in the bottom substrate. The present study suggested that Station I was an appropriate area for the growth and reproduction of green mussels.